Comparison of Quantification Methods of111In-Labelled Platelet Deposition in Peripheral Bypass Grafts - Mortelmans, L.; Verbruggen, A.; De Bakker, C.; Vandecruys, A.; Joosten, J.; Nevelsteen, A.; Noyez, L.; Verstraete, M.; Vermylen, J.; De Roo, M. (Nuklearmedizin - NuclearMedicine, 1987)
The action of antithrombotic drugs can be evaluated by measuring the deposition of111In-labelled platelets on peripheral bypass grafts several days after injection. This evaluation can be performed qualitatively (visual interpretation on the daily images) or quantitatively. Four different methods which calculate the ratio of platelet uptake with a reference region are compared: two methods use a gamma camera and two a detector. A blood sample or the region under the sternal angle are used as reference. The daily ratio of the counts, recorded by a gamma camera in a region of interest covering the graft, and the blood radioactivity interpolated from a platelet survival curve appears to be the most reliable method. The information of all the ratios can be combined in a single thrombogenicity index which reflects the daily rise of a linear or exponential regression versus time.